PELAKSANAAN PEMBELAJARAN PRAKARYA DAN KEWIRAUSAHAAN DENGAN KURIKULUM 2013 - Cahyo Pamungkas; Budi Sutrisno (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2014)
The aims of the research are to: 1) to reveal characteristics of learning business and pre practice lesson, 2) to reveal learning method application, 3) to reveal learning result. The kind of result is qualitative with ethnography design. The research subject at SMA N 1, Teras is Teachers of business and pre practice lesson, and students of class X.IPA-1 and X.IPA-2. While the researches object is learning business and pre practice lesson activity. Data collecting used are: observation, interview, and documentation. Data validity is conducted by using interactive model through reduction process, then drawing conclusion and presenting in valid data form. The research result of business/entrepreneurship at SMA 1, Teras: 1) Interaction of learning business and pre practice lesson was done conductively supported by appropriate media and learning method that is used and teachers’ lovely personality, 2) Media that is usually used on learning activity is audio visual, 3) The main obstacle on conducting learning activity is lack of literature and supporting equipment for doing job and the location for it, 4) The most effective learning method that can be applied is turning on video and group demonstration, 5) Learning result by using scientific approach is the beginning of students business spirit and motivation.